KORELASI INDIKATOR PENILAIAN PEMERINGKATAN WEBSITE PERGURUAN TINGGI WEBOMETRICS DAN 4ICU - Kurniawijaya, Putu Andhika; Wiharta, Dewa Made; Sastra, Nyoman Putra (LPPM STMIK STIKOM Indonesia, 2019)
Colleges in Indonesia as part of an educational institution that seeks to improve the competitiveness of globally through the utilization of ICT (information and communication technology) has been aware of the importance of the website as a key component of the assessment in an effort to align ourselves as a global standard of the College. The instruments most frequently used by universities as reference materials to evaluate performance and productivity based on his/her website is through a college assessor database world, including Webometrics and 4ICU. Correlation between linking Webometrics and 4ICU are aimed to assist colleges in analyzing the quality of traffic services in the field of scientific publications in order to be able to compete in the global sphere and certainly for the better. The methodology used by using spearman rank correlation against major # 29 University according to the webometrics ranking based on 4ICU and 29 top-rated website 4ICU. The results of the research there is a relationship or a significant correlation between the webometrics ranking indicator with indicator correlation value 4ICU ranking of 0.591 contains the category strong enough.